2016
DOI: 10.1007/s12325-016-0309-6
|View full text |Cite
|
Sign up to set email alerts
|

Once-Monthly Continuous Erythropoietin Receptor Activator (C.E.R.A.) in Patients with Hemodialysis-Dependent Chronic Kidney Disease: Pooled Data from Phase III Trials

Abstract: IntroductionErythropoiesis-stimulating agents and iron are commonly used in patients with chronic kidney disease with the aim of correcting anemia and maintaining stable hemoglobin levels. We analyzed pooled data from 13 studies with similar designs included in the Umbrella Continuous Erythropoietin Receptor Activator (C.E.R.A.) program to investigate the effects of continuous erythropoiesis receptor activator in clinically relevant subgroups of patients with chronic kidney disease and to determine whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…To wit, we observed that nearly 70% of European facilities use more than 1 ESA type, and nearly 30% use 3 or more. Comparative studies of established ESA products have generally been unable to detect substantial differences in efficacy or safety outcomes [11][12][13]. The decision to use 1 ESA over another can thus be summarized by several other factors: chiefly cost, availability, and preferences for dosing fre- quency [14].…”
Section: Discussionmentioning
confidence: 99%
“…To wit, we observed that nearly 70% of European facilities use more than 1 ESA type, and nearly 30% use 3 or more. Comparative studies of established ESA products have generally been unable to detect substantial differences in efficacy or safety outcomes [11][12][13]. The decision to use 1 ESA over another can thus be summarized by several other factors: chiefly cost, availability, and preferences for dosing fre- quency [14].…”
Section: Discussionmentioning
confidence: 99%
“…C.E.R.A. is also characterized by high effectiveness in the treatment of renal anemia in dialysis patients, and non-inferiority to other ESAs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most end-stage kidney disease (ESKD) patients on maintenance hemodialysis (HD) are affected by anemia and receive erythropoiesis-stimulating agents (ESAs) to maintain hemoglobin levels in target range. Long-acting ESAs, such as darbepoetin and epoetin beta pegol, have a longer half-life and thus can be administered less frequently than short-acting ESAs, such as epoetin alfa and epoetin beta, which can simplify nurses' work in HD centers and may contribute to better hemoglobin stability (1,2). Both long-and short-acting ESAs are used commonly in the maintenance HD setting, but head-to-head safety comparisons have been uncommon, with a meta-analysis of randomized trials yielding inconclusive results (3).…”
Section: Introductionmentioning
confidence: 99%